The Influence of Fake Reviews on Consumer Perceptions of Risks and Purchase Intentions - Wu, Shijun; Wingate, Nikki; Wang, Zhaoyue; Liu, Qi (Journal of Marketing Development and Competitiveness, 2019)
Online reviews are powerful; but not all of them are authentic. The current research focuses on what we term as Fake Reviews and proposes a conceptual model to delineate the relationship among Fake Reviews, consumer perceptions of risks, and purchase intentions. We classify Fake Reviews into Useless Reviews (Non-review Content and Advertising Content) and False Reviews (Shameless Promotion and Malicious Slander). Analyzing responses of 245 Chinese consumers, the current research demonstrates the influence of Fake Reviews on consumer perceptions of risks, which in turn affect consumer purchase intentions.